The Development of a New and Improved Hurricane Scale for the North Atlantic - Masson, Athena (2018)
The Saffir-Simpson Hurricane Scale (SSHS) was developed in 1969 by Herbert Saffir and Bob Simpson and introduced to the public in 1973. Saffir developed the initial scale when he realized there was no simple scale for describing the effects of hurricanes. He devised a 1-5 scale based on the wind speeds of a storm and the expected damage to structures. Simpson collaborated and added on storm surge and pressure (NOAA, 2006a). The National Hurricane Center (NHC) eliminated the components of pressure and storm surge in 2009, transforming it into a pure wind scale known as the Saffir-Simpson Hurricane Wind Scale (SSHWS). According to the NHC dropping all requirements except wind was to “help reduce public confusion about the impacts associated with the various hurricane categories as well as to provide a more scientifically defensible scale” (Schott et al. 2012). The SSHS has been criticized for many years due to the fact that the scale does not take into consideration rain amounts, forward speed, and size of a tropical cyclone, to name a few critical missing parameters. Recent hurricanes such as Hurricane Harvey (2017) that stalled over the Texas and Louisiana coastlines for several days and contributed to historic flooding, damage, and significant loss of life, show that a change needs to be made in the SSHWS. Classifying a tropical cyclone’s strength solely on the maximum wind speeds does not give an accurate representation of the true intensity and threats associated with a storm. In order for a tropical cyclone to be classified more accurately a new hurricane scale is proposed. This thesis examines existing components found in the original SSHS (wind, barometric pressure, and storm surge) as well as new potential elements that will measure an approaching tropical cyclone: size, precipitation, forward speed, and extratropical transition. A new and improved hurricane scale known as the Masson – Gough Hurricane Scale is proposed and assessed, using past tropical cyclones as well as piloting it on a recent hurricane season, 2017. This research is needed for the purpose of more accurate forecasting and for the benefit of public awareness, safety, management, and preparedness. Ph.D.